Research on Key Technology and Implementation of IaaS Resource Pool Disaster Recovery - Wensheng Yao; Jun Li; Heliang Ye; Ning Wan (Dianxin kexue)
This paper describes the principle and application of key technologies of IaaS disaster recovery scene,explores how to build the disaster recovery system of the IaaS resource pool with these key technologies,and explores the basic principles should followed to realizing IaaS resource pool disaster recovery system.